Estudio de prefactibilidad para la instalación de un centro de distribución y almacén de productos de primera necesidad que ofrezca el delivery a través de una aplicación móvil - Huaman Antonio, Fred Senaa (2022)
The main objective of this project is focused on Establishing the technical, economic, financial, social and market viability for the implementation of a staple food delivery service where a large part of the supply chain is handled and supported by through a mobile application. A market study was carried out for which primary and secondary sources were used, applying a survey to analyze population statistics that allowed determining that the most convenient target market is the Districts of La Molina, San Borja and Santiago de Surco of Lima Metropolitana. Also, the most convenient location for the installation of the warehouse was determined, the factors of macro location and micro location were analyzed, being established in the District of Santiago de Surco of Lima Metropolitana (East), due to its proximity to other districts, its largest population density. For the first year, a demand for S/ 19 461 753 Nuevos Soles and the number of 124,840 orders delivered are estimated. With the financial analysis it was determined that the project is economically and financially viable. The economic viability was estimated with the economic NPV of S/2 433 279 Nuevos Soles and the value of the financial IRR is 63%. With regard to the social impact, it will seek a greater scope of basic necessities to all the people who need it in a moment of urgency, In addition, it will help reduce concentrations in closed spaces such as supermarkets or convenience stores. The online store model will also allow multiple vendors to offer products at a reasonable price both to benefit their profit margins and to the general public. It will not generate a negative impact on the environment because the process does not demand polluting processes that harm it, the order will be packed in biodegradable bags, the consumption of water and electricity is low.